Efektivitas Metode Buzz Group terhadap Kemampuan Berpikir Kritis Siswa dalam Pembelajaran PAI - Wahyuni, Sri Fitri; Mutiarani Pionera; Ramdhani, Muhammad Tri (Nusa Putra University, 2024)
The Effectiveness of the Buzz Group Method on Students’ Critical Thinking Abilities in PAI Learning ABSTRACT The methods used in teaching Islamic Religious Education (PAI) should create critical thinking in students so they think deeply about Islam. However, PAI instruction in class VIII SMP Negeri 6 Palangka Raya has still not optimally generated students' critical thinking because of the implementation of the conventional method. This study aims to examine the effect of the Buzz group discussion method to improve students’ critical thinking on PAI. This study used a quasi-experimental method with Nonequivalent Pretest-Posttest Control Group Design involving 30 students from two different classes as the subjects. Students’ scores from the pretest and posttest became the data needed. The data was then analyzed through the Independent Sample T-test using SPPS 19. The results of the study showed that a significant effect of Buzz group implementation to improve students’ critical thinking in which t count 3.632 > t table 1.701 with the significance value 0.001 < 0.05. Hence, Ha was accepted. In addition, the students’ response questionnaire obtained an average percentage value of 71% showing that the instructional process was in the “good” category.